Revisiting the Paraquat-Induced Sporadic Parkinson's Disease-Like Model - Bastias-Candia, Sussy; Zolezzi Moraga, Juan Manuel; Inestrosa, Nibaldo C. (My University, 2019)
Parkinson's disease (PD) is a major neurodegenerative disorder that affects 1-2% of the total global population. Despite its high prevalence and publication of several studies focused on understanding its pathology, an effective treatment that stops and/or reverses the damage to dopaminergic neurons is unavailable. Similar to other neurodegenerative disorders, PD etiology may be linked to several factors, including genetic susceptibility and environmental elements. Regarding environmental factors, several neurotoxic pollutants, including 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), have been identified. Moreover, some pesticides/herbicides, such as rotenone, paraquat (PQ), maneb (MB), and mancozeb (MZ), cause neurotoxicity and induce a PD-like pathology. Based on these findings, several in vitro and in vivo PD-like models have been developed to understand the pathophysiology of PD and evaluate different therapeutic strategies to fight dopaminergic neurodegeneration. 6-OHDA and MPTP are common models used in PD research, and pesticide-based approaches have become secondary models of study. However, some herbicides, such as PQ, are commonly used by farming laborers in developing countries. Thus, the present review summarizes the relevant scientific background regarding the use and effects of chronic exposure to PQ in the context of PD. Similarly, we discuss the relevance of PD-like models developed using this agrochemical compound.
Keywords: paraquat; pesticides; agrochemicals; parkinson's disease; neurodegeneration